APPLICATION OF NANOMATERIALS FOR SYNTHESIS OF HIGH-TEMPERATURE PHASE IN NONSTICK COVERINGS - D. M. Kukuj; Ju. A. Nikolajchik (Литьë и металлургия)
Matters on possibility of increase of efficiency the nonstick coverings by means of using nanomaterials in their structures of are discussed. Nanomaterials enable to intensify course of reactions of formation of erosion-resistant phase of mullite which increases high-temperature cohesive solidity of the nonstick coverings.